Secondary hemophagocytic lymphohistiocytosis in a 5-month-old infant with IBD post-COVID-19: a case report - Chen, Yulin; He, Xiaoli; Li, Deyuan; Qiao, Lina; Lu, Guoyan (Frontiers in Pediatrics, 2025)
BackgroundCOVID-19 is known to induce cytokine storms and inappropriate cytotoxic immune responses. Hemophagocytic lymphohistiocytosis (HLH) is an underrecognized condition due to a hyperinflammatory syndrome characterized by fulminant hypercytokinemia with a high mortality burden. Cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) induced secondary HLH during and post-infection have been sparsely reported in children. Inflammatory bowel disease (IBD) is a chronic, relapsing disorder of the gastrointestinal tract with a multifactorial etiology involving genetic, environmental, and immunological factors. To date, secondary HLH associated with COVID-19 in very early-onset inflammatory bowel disease (VEO-IBD) has not been reported. This case report aims to enhance understanding of the clinical manifestations of VEO-IBD and HLH, thereby facilitating the timely diagnosis and management of this rare condition.Case presentationWe present the case of a 5-month-old Chinese female infant diagnosed with HLH following COVID-19 infection. The patient presented with hemophagocytic syndrome, which included recurrent fever, hepatosplenomegaly, cytopenia, hyperferritinemia, hypertriglyceridemia, and hypofibrinogenemia, after exposure to her mother, who had been diagnosed with COVID-19. Whole-exome sequencing(WES) identified heterozygous mutations in the IL-10RA gene: c.537 G > A (inherited from her mother) and c.301 C > T (inherited from her father), who was ultimately identified as having VEO-IBD. Despite receiving nutritional support, intravenous immunoglobulin (IVIG), and dexamethasone therapy, the patient continued to experience anemia, diarrhea, and refractory gastrointestinal bleeding. Following a brief improvement after interventional treatment, the parents declined further medical interventions, signed for discharge, and the infant sadly passed away three months later.ConclusionRare genetic variants play a pivotal role in the pathogenesis of VEO-IBD, particularly in infants diagnosed before the age of one. These cases often demonstrate resistance to various immunosuppressive therapies and have a poor prognosis with conventional treatments. Our findings highlight the potential increased risk of severe HLH in patients with VEO-IBD and concurrent COVID-19, underscoring the need for comprehensive and vigilant differential diagnosis when patients exhibit symptoms suggestive of multi-organ damage.